Production of giant gourami Osphronemus goramy Lac. juvenile with different rate of water exchange - Budiardi, Tatag; Ginting, Rona Albrettico Nemanita; Hadiroseyani, Yani (Jurnal Akuakultur Indonesia, 2011)
ABSTRACTGiant gourami Osphronemus goramy Lac. is one of the most important fresh water fish commodities with increasing production level every year. Water quality management through a proper water exchange both in quantity and quality can be one of the alternatives to support the elevating production. This research was conducted from July to August 2010 at the Aquaculture Production Technology and Management Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine Science, Bogor Agricultural University. The juvenile used was 0.84±0.011 cm in length and 0.017±0.001 cm in weight which reared in nine units of aquaria with a size of 60×29×33 cm3. Silk worm was used as the feed and provided daily at satiation. Water exchange was performed twice a day at a level depending on the treatment, namely 75% (50% at morning and 25% at evening), 100% (50% at morning and evening) and 125% (75% at morning and 50% at evening) of total water volume. Water exchange at 75%, 100%, and 125%/day resulted in survival rates of 94.11±0.63%; 91.89±2.02%; and 93.89±0.75%; specific growth rates of 7.43±0.15%, 8.58±0.24%, and 9.97±0.18%. Growth rate in length of 1.06±0.06 cm, 1.33±0.04 cm, and 1.55±0.01 cm; coefficient of variation in length of 11.31±1.43%, 9.35±1.46%, and 6.90±2.30%; feed efficiency of 12.47±0.30%, 14.32±1.05%, and 19.67±0.54%. The financial benefits resulted of the process were worth of IDR.351,903.00; IDR.402,302.00; and IDR.464,715.00; whereas R/C ratio of 1.71; 1.80; dan 1.90; BEP of 1,845 unit, 1,645 unit, and 1,517 unit; payback period (PP) of 0.97 years, 0.85 years, and 0.74 years; and the cost production as much as IDR.79.90; IDR.82.70; and IDR.82.90/individual, respectively. The treatments were significantly different on several parameters, such as specific growth rate, length of growth rate, feed efficiency at p<0.05. The results of this experiment showed that 125% daily water exchange improved the production performance of giant gourami juvenile cultured at a density of 20 fish/L. For production purpose, rearing giant gourami fish 2 cm in size at a density of 20 fish/L was found as the optimum condition through 125%/day water exchange.Keywords: water exchange, survival rate, growth, gourami fishABSTRAKIkan gurami Osphronemus goramy Lac. merupakan salah satu komoditas penting ikan air tawar dengan produksi yang cenderung meningkat dari tahun ke tahun. Pengelolaan kualitas air dengan penggantian air yang tepat secara kualitas dan kuantitas dapat menjadi salah satu jawaban dalam meningkatkan produktivitas budidaya ikan gurami. Benih ikan yang digunakan dalam penelitian berukuran panjang rata-rata 0,84±0,011 cm dan bobot tubuh rata-rata 0,017±0,001. Wadah yang digunakan berupa akuarium berukuran 60×29×33 cm3 sebanyak sembilan unit, dengan kepadatan 20 ekor/L. Pakan yang diberikan berupa cacing sutra secara at satiation. Perlakuan berupa pergantian air yaitu: 75% (50% pagi dan 25% sore), 100% (50% pagi dan 50% sore) dan 125% (75% pagi dan 50% sore) dari total volume air pemeliharaan. Setiap perlakuan diulang tiga kali. Hasil penelitian menunjukkan bahwa pergantian air berpengaruh nyata (p<0,05) terhadap laju pertumbuhan bobot dan panjang, serta efisiensi pakan, sedangkan kelangsungan hidup dan koefisien keragaman panjang tidak berbeda nyata antar perlakuan (p>0,05). Laju pertumbuhan dan efisiensi pakan tertinggi (p<0,05) diperoleh pada perlakuan pergantian air 125%, yaitu laju pertumbuhan bobot 9,97±0,18%, pertumbuhan panjang mutlak 1,55±0,01 cm, dan efisiensi pakan 19,67±0,54%. Kelangsungan hidup benih ikan gurami berkisar antara 91,89‒94,11. Pemeliharaan benih ikan gurami dengan mengganti air 125%/hari juga memberikan keuntungan tertinggi, yakni Rp464.715,-. Dengan demikian, pendederan benih ikan gurami sebaiknya dilakukan dengan pergantian air 125%/hari.Kata kunci: pergantian air, kelangsungan hidup, pertumbuhan, ikan gurami